Blue extreme disk-runaway stars with Gaia EDR3 - Irrgang, Andreas; Dimpel, Markus; Heber, Ulrich; Raddi, Roberto (Astronomy & Astrophysics, 2021)
Since the discovery of hypervelocity stars in 2005, it has been widely believed that only the disruption of a binary system by a supermassive black hole at the Galactic center (GC), that is, the so-called Hills mechanism, is capable of accelerating stars to beyond the Galactic escape velocity. In the meantime, however, driven by the Gaia space mission, there is mounting evidence that many of the most extreme high-velocity early-type stars at high Galactic latitudes do originate in the Galactic disk and not in the GC. Moreover, the ejection velocities of these extreme disk-runaway stars exceed the predicted limits of the classical scenarios for the production of runaway stars. Based on proper motions from the Gaia early data release 3 and on recent and new spectrophotometric distances, we studied the kinematics of 30 such extreme disk-runaway stars, allowing us to deduce their spatial origins in and their ejection velocities from the Galactic disk with unprecedented precision. Only three stars in the sample have past trajectories that are consistent with an origin in the GC, most notably S5-HVS 1, which is the most extreme object in the sample by far. All other program stars are shown to be disk runaways with ejection velocities that sharply contrast at least with classical ejection scenarios. They include HVS 5 and HVS 6, which are both gravitationally unbound to the Milky Way. While most stars originate from within a galactocentric radius of 15 kpc, which corresponds to the observed extent of the spiral arms, a group of five stars stems from radii of about 21-29 kpc. This indicates a possible link to outer Galactic rings and a potential origin from infalling satellite galaxies.
CRIS-Team Scopus Importer:2021-04-09
Keywords: Stars: distances; Stars: early-type; Stars: fundamental parameters; Stars: kinematics and dynamics